Age modulates the effect of COMT genotype on delay discounting behavior - Smith, Christopher T. (2012)
RATIONALE AND OBJECTIVE: A form of impulsivity, the tendency to choose immediate over delayed rewards (delay-discounting) has been associated with a single nucleotide polymorphism (SNP) in the catechol-O-methyltransferase (COMT) gene (COMTval(158)met; rs4680). However, existing data regarding the nature of this association conflicts. We have previously reported that adults homozygous for valine (val) at the COMTval(158)met SNP demonstrate greater delay-discounting than do methionine (met) allele carriers (Boettiger et al. 2007). In contrast, a recent study of adolescent males found that those with the met/met genotype demonstrate greater delay-discounting than do val-allele carriers (Paloyelis et al. 2010). Based on reported age-related changes in frontal dopamine function and COMT expression, we hypothesized that the association of COMT genotype with delay-discounting behavior is modulated by age from late adolescence to young adulthood. METHODS: To test this hypothesis, we genotyped late adolescents (18–21 years; n=72) and adults (22–40 years; n=70) for the COMTval(158)met polymorphism, measured their delay-discounting behavior, and tested for an interaction between age group and COMT genotype. RESULTS: This cross-sectional study found that age modulates COMTval(158)met genotype effects on delay-discounting behavior. Among met-carriers, delay-discounting was negatively correlated with age from late adolescence to adulthood, while among val/val individuals delay-discounting was positively correlated with age across this range. CONCLUSIONS: These results confirm our previous finding of enhanced delay-discounting among val/val adults relative to met-allele carriers, and help reconcile existing literature. We propose a single U-shaped model of the relationship between frontal DA levels and impulsive choice that accounts for both adolescent and adult data.